Comparison of conventional heat-treated and membrane filtered infant formulas using an in vitro semi-dynamic digestion method. Issue 15 (12th July 2022) - Chen, Yihong; Callanan, Michael; Giblin, Linda; Tobin, John; Brodkorb, André
Abstract : Introducing membrane filtration steps into infant milk formula (IMF) manufacture can partly preserve native whey proteins in the final products. Abstract : Introducing membrane filtration steps into infant milk formula (IMF) manufacture can partly preserve native whey proteins in the final products. In this study, the IMF produced by membrane filtration (MEM-IMF) and conventional heat treatment (HT-IMF) were compared by using a novel semi-dynamic infant in vitro digestion method. MEM-IMF exhibited a fragmented curd during gastric digestion, and confocal laser light microscopy showed that protein aggregates had disassociated from the fat droplets within 93 min in the MEM-IMF digesta. In contrast, the digesta of HT-IMF showed a more extensive curd formation and denser protein aggregates, which remained intact until the end of gastric digestion. Molecular weight profiles and the primary amine assay suggested that protein degradation and peptide release were faster in the MEM-IMF. In conclusion, the presence of native whey protein in the IMF altered the gastric digestion kinetics by changing coagulation and formation of aggregates, potentially accelerating the rate of gastric emptying in vivo .